From grass to grace: How SLMTA revolutionised the Bamenda Regional Hospital Laboratory in Cameroon - Siyem C. Nkwawir; Nakeli N. Batumani; Talkmore Maruta; Charles N. Awasom (AOSIS, 2014)
Background: Public health laboratories form the foundation on which today's clinical laboratory practice in Cameroon is built. The advent of the Strengthening Laboratory Management Toward Accreditation (SLMTA) programme in 2009 empowered the Bamenda Regional Hospital Laboratory (BRHL) to improve its working culture, practices and management. Objectives: To evaluate the results of SLMTA implementation at BRHL and discuss lessons learned. Method: In 2010, the SLMTA programme was rolled out in Cameroon to improve laboratory quality management systems in five laboratories, including BRHL. Three workshops were conducted (the first centralised, the remaining two on-site at each laboratory) and improvement projects were implemented after each workshop with the assistance of mentors. Audits were used in order to evaluate performance and to identify areas for further improvement. Results: BRHL had the lowest score (18%) amongst the cohort at the baseline audit and the highest (81%) at the official Stepwise Laboratory Quality Improvement Process Towards Accreditation (SLIPTA) audit conducted in August 2013 by the African Society for Laboratory Medicine. Improvements were observed in each of the 12 Quality System Essentials; improvement was especially noteworthy in the areas of facilities and safety, and purchasing and inventory. Staff investment and pride in the quality of laboratory services increased. Conclusion: BRHL's remarkable improvement was achieved with a combination of SLMTA training activities, intensive on-site mentorship and the collective focus of all laboratory staff. The experience at Bamenda Hospital illustrates what can be achieved when a laboratory successfully harnesses the energy of its staff and implements changes to improve the quality of services in a transformation taking them from grass to grace.